Restorative Justice and Dialogue: Impact, Opportunities, and Challenges in the Global Community - Mark S. Umbreit; Marilyn Peterson Armour (Washington University Journal of Law & Policy, 2011)
The Article focuses on the Community of Veterans Engaged in Restoration (COVER) restorative justice program offered by the Sheriff's Department of San Francisco, California. Information is provided on how the program aims to prevent crimes by U.S. veterans, focuses on offender accountability, and promotes community involvement.
Keywords: Restorative justice; Criminal justice administration; Youth crime -- Prevention; Howard Zehr; Changing Lenses: A New Focus for Crime & Justice (Book)